2013
DOI: 10.1038/ncomms2548
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic switching of ferroelectric domains at room temperature in multiferroic PZTFT

Abstract: Single-phase magnetoelectric multiferroics are ferroelectric materials that display some form of magnetism. In addition, magnetic and ferroelectric order parameters are not independent of one another. Thus, the application of either an electric or magnetic field simultaneously alters both the electrical dipole configuration and the magnetic state of the material. The technological possibilities that could arise from magnetoelectric multiferroics are considerable and a range of functional devices has already be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(157 citation statements)
references
References 41 publications
7
142
2
Order By: Relevance
“…Evans et al 50 measure 5.5 Â 10 À8 sm À1 to 1.3 Â 10 À7 sm À1 for a 31 in 40:60 PFT/PZT at 293 K. These are very large values. We note also for completeness that PFN-PZT ceramic single-phase compounds were first studied in 1981 by Whatmore and Bell.…”
Section: Discussionmentioning
confidence: 99%
“…Evans et al 50 measure 5.5 Â 10 À8 sm À1 to 1.3 Â 10 À7 sm À1 for a 31 in 40:60 PFT/PZT at 293 K. These are very large values. We note also for completeness that PFN-PZT ceramic single-phase compounds were first studied in 1981 by Whatmore and Bell.…”
Section: Discussionmentioning
confidence: 99%
“…In combination with PZT, its properties are not significantly dependent upon the Zr/Ti ratio; and in fact, pure PbTiO 3 works as well as PZT for most of these systems, as initially demonstrated with PFW. 53 Switching in PFT/PZT single-phase nano-crystals was reported by Evans et al, 54 as shown in Figure 8, using a submicron-diameter sample cut via focused-ion beam from a one-micron diameter grain in a bulk ball-milled ceramic. All tests show these samples to be single-phase, although under highresolution transmission electron microscopy some dark nano-spots were observed decorating the grain boundary.…”
Section: Lead-iron Perovskitesmentioning
confidence: 99%
“…25% P, and subsequent field reversals switch negligible amounts of polarization. 54 This implies either that the magnetically switched electric domains are somehow more easily pinned or that another mechanism is involved, possibly involving the nested ferroelastic twins and magnetostriction. One can switch from þ P to ÀP (a large value of ca.…”
Section: Lead-iron Perovskitesmentioning
confidence: 99%
“…That is, electronic conduction is similar to fluid dynamics, with vortex motion, and not limited by Bloch theory. At about the same time it was shown [3][4][5] that the ferroelastic domain walls in multiferroics 6 are also controlled by fluid mechanics, with both wrinkling [7][8][9] and folding 3,4 at certain velocity thresholds, and hence that the domain walls may be treated as ballistic objects in high-viscosity media [n.b., wrinkling involves smoothly curved periodic modulation of domain walls, whereas folding consists of nearly 180-degree changes in direction] . In this sense semi-classical convection processes seem to appear in systems with very different basic dynamics.…”
Section: P2mentioning
confidence: 99%